e i θ e 2 i θ e 3 i θ . . . e n i θ = 1
Find the value of θ satisfying the above equation for m ∈ N .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
e i θ . e 2 i θ ⋯ e n i θ = ( cos θ + i sin θ ) ( cos 2 θ + i sin 2 θ ) ⋯ ( cos n θ + i sin n θ )
Using De Moivre's Theorem, the above expression can be written as
( cos θ + i sin θ ) 1 + 2 + 3 + ⋯ + n = ( cos θ + i sin θ ) 2 n ( n + 1 ) = cos ( 2 n ( n + 1 ) θ ) + i sin ( 2 n ( n + 1 ) θ )
which is equal to 1 (as given in the statement of the problem) and further we can write 1 as ( c o s 0 + i sin 0 ) .
Therefore we have cos ( 2 n ( n + 1 ) θ ) + i sin ( 2 n ( n + 1 ) θ ) ⇒ c o s ( 2 n ( n + 1 ) θ ) = c o s 0 2 n ( n + 1 ) θ = 2 m π ± 0 .
Hence θ = n ( n + 1 ) 4 m π . □
The problem statement should not mention "m" at all. The parameter "m" is introduced during the process of solution in order to index the multiple values of theta that will satisfy the equation.
Why can't we do sin x =0 and x=mπ Thus we get ans just half of original
Problem Loading...
Note Loading...
Set Loading...
1 = e 2 m π i
L . H . S = e i × θ × ( 2 n ( n + 1 ) ) = 1 = e 2 m π i
θ = n ( n + 1 ) 4 m π